Results from Chile's 2022 report card on physical activity for children and adolescents - Nicolas Aguilar-Farias; Sebastian Miranda-Marquez; Marcelo Toledo-Vargas; Kabir P. Sadarangani; Jessica Ibarra-Mora; Pia Martino-Fuentealba; Jaime Carcamo-Oyarzun; Carlos Cristi-Montero; Fernando Rodríguez-Rodríguez; Paula Guarda-Saavedra; Teresa Balboa-Castillo; Astrid Von Oetinger; et al. (Journal of Exercise Science & Fitness)
Background/Objective: To summarize the results of Chile's 2022 Report Card (RC) on physical activity (PA) for Children and Adolescents. Methods: Chile's 2022 RC included ten core PA indicators common to the Global Matrix 4.0. Evidence from scientific articles, reports, and databases published between 2018 and January 2022 was included for each indicator. The data were collected and analyzed by a national scientific committee, which assigned letter grades (A to F) using a consensus based on benchmarks defined and revised by the Active Healthy Kids Global Alliance. Results: The committee assigned the following grades: Overall PA, D−; Organized Sports and Physical Activity Participation, C−; Active Play, Incomplete; Active Transportation, D; Sedentary Behavior, D−; Physical Fitness, Incomplete; Family and Peers, D; School, C; Community and Environment, D+; Government, A−. Conclusions: Chile's 2022 RC, like its previous versions, shows persistently low grades for most indicators. Overall PA remained nearly unchanged, while Community and Environment scored lower. Slight improvements were seen in Organized Sports, Family and Peers, and School Environment. While Chile has endeavored to increase children's activity levels, policies require implementation through a systemic, coherent framework to promote sustainable changes and reach a larger portion of children and youth.